Pengaruh Penjualan dan Beban Pokok Penjualan Terhadap Laba Bersih: (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar & Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021) - Suci Tri Wahyuni; Debbie Christine (Owner : Riset dan Jurnal Akuntansi, 2023)
Manufacturing Industry is one of the factors supporting the economic growth, including the sector of basic and chemical industries. Every company will try to make profits, sales and cost of sales are including the factors can influence profit-making. The purpose of this research is to investigate the influence of sales and cost of sales in partial and simultaneous manner to net profits in manufacturing companies at the sector of basic and chemical industries registered in Indonesia Stock Exchange during the period of 2018-2021. The variables tested in this research are sales and cost of sales is the independent variable while the dependent variable is net profits. The method used in this research is the associative method. The number of populations in this research is 75 manufacturing companies at the sector of basic and chemical industries registered in Indonesia Stock Exchange during the period of 2018-2021. The method of sampling selection used is purposive sampling so that 26 samples are taken to be analyzed. The data analysis is conducted by using panel data regression. The program used for data processing is EViews 12. The results of this research indicate that partially sales and cost of sales influence on the net profits, and simultaneously sales and cost of sales have significant influence on the net profit by 62,1488%.